Affective Disturbances During Withdrawal from Chronic Intermittent Ethanol Inhalation in C57BL/6J and DBA/2J Male Mice. (21st May 2018) - Sidhu, Harpreet; Kreifeldt, Max; Contet, Candice
Abstract : Background: Alcohol use disorders are characterized by a complex behavioral symptomatology, which includes the loss of control over alcohol consumption and the emergence of a negative affective state when alcohol is not consumed. Some of these symptoms can be recapitulated in rodent models, for instance following chronic intermittent ethanol (EtOH; CIE) vapor inhalation. However, the detection of negative affect in mice withdrawn from CIE has proven challenging and variable between strains. This study aimed to detect reliable indices of negative emotionality in CIE‐exposed C57BL/6J (C57) and DBA/2J (DBA) mice. Males were used because they are known to escalate their voluntary EtOH consumption upon CIE exposure, which is hypothesized to be driven by negative reinforcement (relief from negative affect). Methods: Adult male mice were exposed to 4 to 6 weeks of CIE and were evaluated 3 to 10 days into withdrawal in the social approach, novelty‐suppressed feeding, digging, marble burying, and bottle brush tests. Results: Withdrawal from CIE decreased sociability in DBA mice but not in C57 mice. Conversely, hyponeophagia was exacerbated by CIE in C57 mice but not in DBA mice. Withdrawal from CIE robustly increased digging activity in both strains, even in the absence of marbles. Aggressive responses to bottle brush attacks were elevated in both C57 and DBA mice following CIE exposure, but CIE had an opposite effect on defensive responses in the 2 strains (increase in C57 vs. decrease in DBA). Conclusions: Our results indicate that withdrawal from CIE elicits negative emotionality in both C57 and DBA mice, but different tests need to be used to measure the anxiogenic‐like effects of withdrawal in each strain. Increased digging activity and irritability‐like behavior represent novel indices of affective dysfunction associated with withdrawal from CIE in both mouse strains. Our findings enrich the characterization of the affective symptomatology of protracted withdrawal from CIE in mice. Abstract : Our study aimed to identify signs of negative affect in mice experiencing alcohol withdrawal following several weeks of chronic intermittent ethanol vapor inhalation. We compared 2 strains of mice and found that different behavioral tests were needed to capture anxiety‐like behavior in each strain. Interestingly, digging activity increased in both strains and, while the exact nature of the affective state associated with excessive digging is unknown, it represents a novel index of affective disturbance during protracted withdrawal from alcohol.